Integration Through Health During Protracted Displacement: Case Studies From Colombia and Jordan. (March 2023) - McCann, Katherine; Fouad, Fouad M.; Harker Roa, Arturo; Zard, Monette
As the global rate of displacement reaches new highs and the average length of displacement extends from years to decades, integration is an increasingly crucial lifeline for refugees and displaced communities seeking to rebuild their lives. Health systems serve as an ideal conduit for integration due to universal need, system complexity, and the interplay of political, social, and economic factors on health outcomes. Using lessons learned from case studies in Colombia and Jordan, this paper will explore different strategies for integration of refugee health services with host population health systems. It will highlight successful policy implementation and innovative approaches as well as predict potential barriers to success via a population-centered approach that emphasizes the importance of supporting host communities concurrently with displaced populations. It offers the following findings and recommendations for governmental and humanitarian actors. Effective integration requires a "whole of person" approach which acknowledges and responds to the linkages between legal status, economic needs, and mental and physical health and wellbeing. Addressing the health needs of populations experiencing protracted displacement must go hand-in-hand with, and cannot be decoupled from, addressing the needs of host communities. Demographic and epidemiologic data inclusive of both host and displaced populations enables governments and service providers to better plan for and respond to key health and non-health needs. Donors and financing structures can play a critical role in facilitating greater integration of health and other services.